PENGARUH PENGAWASAN KOMITE AUDIT, AUDIT INTERNAL, AUDIT EKSTERNAL TERHADAP KESEHATAN KEUANGAN PERUSAHAAN DAN DAMPAKNYA TERHADAP PROFITABILITAS - Merawati, Endang Etty; Hatta, Iha Haryani (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2014)
Insurance and reinsurance companies are required, to maintain a soundfinancial standing and comply with the provisions on the companies equity as stipulatedÃ‚Â by the government. To achieve such equity, the companies must retain theirÃ‚Â profitability. Under a supervision system supported by the audit committee, internalÃ‚Â auditor and external auditor, it is expected that the insurance companies shall be able toÃ‚Â fulfill their obligation in complying with all the prevailing regulations. If these companies fail to do so, the companies shall be subject to the supervision by the government. This study was conducted on insurance and reinsurance companies listedÃ‚Â in the Indonesian Stock Exchange in 2012 (11 companies). Thirty eight high officials ofÃ‚Â the top management of the companies were interviewed as respondents. By applyingÃ‚Â the SPSS program the results showed that there are significant relations among theÃ‚Â audit committee, the internal and external auditor in supervising the operations of theÃ‚Â insurance companies. There is a positive correlation between the audit committee andÃ‚Â the internal auditor; and there is a positive correlation between the audit committee andÃ‚Â the external auditor whereas there is also a positive correlation between the internalÃ‚Â auditor and the external auditor. Simultaneous influence of the audit committee, theÃ‚Â internal audit and the external audit shows a positive effect on the financial soundness.Ã‚Â However, external audit has only partial influence on the financial soundness. TheÃ‚Â simultaneous influence of audit committee, audit internal, audit external and financialÃ‚Â soundness shows a significant effect on the profitability. The partial influence on eachÃ‚Â independent variabel (mentioned above) has a significant effect on the profitability.